ANALISIS FINANCIAL DISTRESS PADA PT BANK MUAMALAT INDONESIA TBK PERIODE 2014 - 2018 - Adinugrah S. Ully Weo; Paulina Yuritha Amtiran; Fransina W Ballo (Universitas Nusa Cendana, 2022)
Financial distress is a condition where the company experiences financial difficulties which can indicate bankruptcy. This study aims to determine the level of financial distress at Bank Muamalat Indonesia for the period 2014-2018. This type of research is a quantitative descriptive study using secondary data in the form of financial statements during 2014-2018. The data analysis technique in this study is the modified Altman Z-Score analysis technique with the formula Z = 6. 56X1 + 3. 26X2 + 6. 72X3 + 1. 05X4. With the assessment criteria Z > 2.6, it means that the company is in the Safe zone or healthy category. 1.1 Z 2.6 are categorized in the Gray Zone or doubtful. Z-Score 1.1, which means the company is in the Distress category and has the potential to go bankrupt. The results showed that the financial condition of Bank Muamalat Indonesia in 2014 and 2017 was in the safe zone or healthy category. In 2015, 2016, and 2018 the financial condition of Bank Muamalat Indonesia was in the gray zone category or doubtful. The financial condition during the study period was not in the distress category. This condition can make the company depressed if the management does not make improvements to the company's financial performance because the company is not in a healthy financial condition. Keywords : Altman Z-Score, EBIT, Book Value of Debt, Book Value of Equity, Financial Distress, Retained Earnings, Working Capital